The Influence of Mass Media and Friends' Association on Student Delinquency in Public Elementary School 1 Purbasari Purbalingga - Nur Istinganah; Ristiana Dyah Purbandari (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to investigates the impact of globalization on the declining character of children, focusing on the escalation of student delinquency influenced by mass media exposure and friendship dynamics among elementary school students. Employing a quantitative Cross-Sectional design and Total Sampling technique, data from 20 respondents were gathered through questionnaires and checklists to measure mass media consumption, friendship quality, and delinquent behavior. Statistical analyses, including the F-test and t-test, revealed that mass media exposure and friendship dynamics collectively accounted for 63.7% of the variance in student delinquency. These findings highlight the need for collaborative efforts between schools and parents to combat student delinquency, with implications for targeted interventions and educational initiatives to promote positive behavior among youth. Further research is warranted to explore the nuanced influences of mass media and friendships on student behavior and societal well-being.